Continuous, pilot-scale production of carbon fiber from a textile grade PAN polymer. (June 2022) - Khan, Huma; Kaur, Jasjeet; Naebe, Minoo; Hutchinson, Sally; Varley, Russell J.
Abstract: Presented here is an investigation into the successful wet spinning and carbonization of a low-cost textile grade (TG-PAN) polyacrylonitrile (PAN) polymer blended with a more traditional carbon fiber (CF-PAN) grade precursor. Both wet spinning and carbonization were performed using continuous pilot scale facilities directly analogous to larger scale industrial processes which provide validation for further scale-up. The blended precursor fibers (TG-CF) showed consistently uniform cross-sections with the benchmark CF grade PAN precursor exhibiting mechanical properties similar to a commercially available precursor fiber. Despite a TG-PAN only precursor failing to adequately stabilize, the benchmark CF-PAN and the blended (TG-CF) precursor fibers and carbon fibers produced are high quality and exhibit uniform properties. The corresponding TG-CF carbon fiber containing 70 wt% of TG-PAN has a tensile strength of 2.2 GPa, a tensile modulus of 210 GPa and a 1% elongation to failure. Although less than the CF-PAN carbon fiber, the mechanical properties of TG-CF affirm that this approach has the potential to develop scalable low-cost carbon fiber suitable for a range of important applications. Graphical Abstract: ga1